2021
DOI: 10.3389/fnins.2021.628403
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Candesartan Treatment Modulates Behavior, Synaptic Protein Levels, and Neuroinflammation in Female Mice That Express Human APOE4

Abstract: Evidence suggests that angiotensin receptor blockers (ARBs) could be beneficial for Alzheimer’s disease (AD) patients independent of any effects on hypertension. However, studies in rodent models directly testing the activity of ARB treatment on behavior and AD-relevent pathology including neuroinflammation, Aβ levels, and cerebrovascular function, have produced mixed results. APOE4 is a major genetic risk factor for AD and has been linked to many of the same functions as those purported to be modulated by ARB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…A separate study reported that inhibition of mGluR5 exerted beneficial effects exclusively in male APP/PS1 mice by decreasing amyloidosis and improving cognition, while no changes were observed in females ( Abd-Elrahman et al, 2020 ). In contrast, the angiotensin receptor blocker, candesartan cilexetil, improved performance in the novel object recognition test and reduced glial activation in female 5xFAD mice crossed with mice that were homozygous for the human APOE4 gene but had no significant effect in males ( Scheinman et al, 2021 ).…”
Section: Sex Differences and Microglia: Neurodegenerative Diseasementioning
confidence: 94%
“…A separate study reported that inhibition of mGluR5 exerted beneficial effects exclusively in male APP/PS1 mice by decreasing amyloidosis and improving cognition, while no changes were observed in females ( Abd-Elrahman et al, 2020 ). In contrast, the angiotensin receptor blocker, candesartan cilexetil, improved performance in the novel object recognition test and reduced glial activation in female 5xFAD mice crossed with mice that were homozygous for the human APOE4 gene but had no significant effect in males ( Scheinman et al, 2021 ).…”
Section: Sex Differences and Microglia: Neurodegenerative Diseasementioning
confidence: 94%
“…Overall, APOE4 is associated with reduced blood flow, increased arteriole stiffness, and enhanced sensitivity to hypertension [ 150 ]. As such, long-term treatment with angiotensin receptor blockers has been shown to improve memory and neuroinflammation independently of Aβ pathology in female mice expressing human APOE4 [ 151 ]. Similarly, research suggests that vascular endothelial growth factor A (VEGFA) is protective against AD in apoE4-TR mice and could be a promising therapeutic target [ 152 ].…”
Section: Pathobiological Function Of Apoementioning
confidence: 99%
“…Estradiol regulates the expression of AT 1 R and ACE activity in several peripheral tissues (105) and mediates dopaminergic cell damage in Parkinson's disease (106). In experimental models of Alzheimer's disease inhibition of the ACE/Ang-II/AT 1 R axis by ARBs (98) or ACEi (82, 84) had higher anti-inflammatory effects in the brain of female mice. In line with these observations, the stimulation of estrogen receptor b counteracts the negative effect of Ang-II on microglial polarization (77), highlighting a potential link between low estrogen levels and Ang-II mediated neuroinflammation in microglia.…”
Section: Ras and Neuroinflammationmentioning
confidence: 99%
“…Recent data indicate that vaccination against Ang-II inhibited astrocytic and microglial activation by stimulating basic fibroblast growth factor 2 (FGF2) signaling, and improved cognitive outcome in rats with vascular dementia ( 59 ). Neuromodulatory effects mediated by microglia and astrocytes have been reported with ARBs ( 82 , 85 , 86 , 95 , 98 100 ) and ACE inhibitors (ACEi) ( 82 ). Also, AT 1 R knock down by viral vector, reduced inflammatory mediators and glial activation in hypertensive rats ( 101 ).…”
Section: Introductionmentioning
confidence: 99%